Mycobacterium bovis Isolates with M. tuberculosis Specific Characteristics - Kubica, Tanja (Centers for Disease Control and Prevention, 2006)
Our study is the first report of exceptional Mycobacterium bovis strains that have some characteristics of M. tuberculosis. The strains were isolated from 8 patients living in Kazakhstan. While molecular markers were typical for M. bovis, growth characteristics and biochemical test results were intermediate between M. bovis and M. tuberculosis.